Interdisciplinaridade e totalidade: perspectivas à luz do materialismo dialético - Santos, Fabrizio Cândia dos (2021)
The present work aims to verify the possibility of a dialogue between interdisciplinarity and totality from a materialistic dialectical approach as opposed to the perspective of subject philosophy. Founded on the complexity axis, the subject's philosophy approach reduces interdisciplinarity to a purely epistemological issue, giving it a status of representation. Conversely, under the perspective of materialist dialectic and founded under the ontological category of totality, scientific disciplines are recovered in their real aspect, as what they are exactly: social relations. Interdisciplinarity, in this case, can only mean a reorganization of the disciplines in their entirety from the revolution of social relations and all the material environment that supports them, solving the epistemological question in ontology. In this step, after a brief historical journey to criticize the current stage of interdisciplinarity, the task of evidencing how an interdisciplinary construction is in the intimate dependence of a dialectical process of man's subjectification is undertaken, insofar as it objective in history. In addition, it seeks to demonstrate that an interdisciplinary meaning is not dissociated from the social relations in which it is produced, and for this very reason, an interdisciplinary production can reveal either a revolution or be just an appendix, a specialization of existing social relations. Finally, it is intended that it will be possible to demonstrate the categories of dialectics in contribution to the construction of an epistemology of a materialist order, determined by an ontology of the social being.